Determinação de ferro em fertilizante por ICP-OES e FAAS: avaliação e estudo de caso dos métodos analíticos - Faria, Fernanda Amaral (Universidade Federal de São Carlos, 2022)
Considering the increase of the world population, which is expected to reach 9.2 billion in 2050 according to the United Nations Organization (UNO), the need for food production may grow 70% by the year of 2050, according to the Food and Agriculture Organization of the United Nations (FAO). Therefore, the demand for food implies the exploration of new areas for agricultural cultivation which are, in general, less fertile and require treatment for soil fertility correction and plant nutrition. In this regard, fertilizers provide nutrients for the growth cycle of plants and, consequently, increase the production of quality food. In the Brazilian scenario, fertilizers are produced and inspected according to the rules of the Ministry of Agriculture, Livestock and Supply (MAPA). For inspection and quality control of fertilizers, MAPA elaborated a Manual of Analytical Methods with suggested methodologies for fertilizer companies to conduct such analyses. The proposed methodologies suggest the use of analytical techniques such as Flame Atomic Absorption Spectrometry ( FAAS) and Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). In this sense, the present work was conducted with the aim to comparatively evaluate the FAAS single-element technique and the ICP-OES multi-element technique for determining the iron content in a fertilizer. A brief review of the concepts over FAAS and ICP-OES and a case study with the evaluation of the analytical parameters for comparative purposes between the techniques enabled the conclusion and choice of FAAS for determination the total value of soluble iron in a fertilizer developed by Oxiquímica.
Determination of iron in fertilizer by ICP-OES and FAAS: evaluation and case study of analytical methods
Keywords: FAAS; ICP-OES; Fertilizantes; Ferro; MAPA; Fertilizers; Iron; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE